Novel thiophene derivatives as eco-friendly corrosion inhibitors for mild steel in 1 M HCl solution: Characterization, electrochemical and computational (DFT and MC simulations) methods. Issue 6 (December 2022) - Fernine, Y.; Arrousse, N.; Haldhar, Rajesh; Raorane, Chaitany Jayprakash; Ech-chihbi, E.; Kim, Seong-Cheol; El Hajjaji, F.; Alami, A.; Touhami, M. Ebn; Taleb, M.
Abstract: Two novel organic aromatic thiophene derivatives, 5-(thiophen-2-yl)− 1 H-tetrazole (TET) and thiophene-2-carbaldehyde oxime (OXM) were investigated for their anticorrosion properties on the mild steel (M-S) in a 1 M HCl media. The two organic inhibitors have significant resistance to the effect of time of immersion, for example, the effectiveness of the molecule TET increases with the increase in time until 12 h and the molecule OXM effectiveness remains almost stable. The adsorption mechanism of OXM and TET was evaluated by electrochemical measurements (polarization and impedance spectroscopy), ultraviolet-visible spectrophotometry (UV–Vis), scanning electron microscopy (SEM) joint with energy dispersive analysis of X-rays (EDAX). The effectiveness of these molecules was significantly influenced by temperature, immersed time, and concentration [10 −6 M − 10 −3 M], reaching a maximum of 94 %, and 95 % for OXM and TET, respectively, at 10 −3 M. In addition, the maximum shift in Ecorr values is 10–17 mV, which implies that the investigated thiophene compounds are mixed-type (anodic/cathodic) inhibitors. SEM micrographs confirmed the formation of a protective layer adsorbed on the M-S surface. The Electrophilic/nucleophilic attacks (Fukui indices) on M-S are theoretically determined. Strong consistency of findings obtained by computational (DFT and MC simulations) and electrochemical tests were demonstrated. Graphical Abstract: ga1 Highlights: Two novel organic thiophene derivatives have been investigated for their anti-corrosive activities. OXM and TET show 94 % and 95 % corrosion inhibition efficiency at 10 −3 M concentrations, respectively. The morphological studies suggest its extraordinary surface adsorption abilities. The theoretical investigations also support the experimental outcomes.